Perancangan aplikasi augmented reality perangkat keras komputer bagi siswa sekolah dasar - Meinardi Trianto, Edwin; John Pattiasina, Timothy; Purnomo Urip, Felipe; Rahmawati, Titasari; Sena, I Gede Wiarta; Soedargo, David Saputra Octadianto (Universitas Muhammadiyah Riau, 2023)
Augmented Reality is a system or form of technological progress and has been used in several things in life. The application of Augmented Reality as a media to support work and learning has been widely used. The use of Augmented Reality technology as a learning medium can support visualization in the field of elementary school education, especially in information and communication technology lessons or what is often known as ICT subjects. The application, called